La silla vacía como mecanismo democrático de participación ciudadana: estudio de caso de la provincia de El Oro-Ecuador - Calderon Atiencie, Karina Elizabeth (2022)
The objective of this research was to determine the characteristics with which the Empty Chair is applied within the Decentralized Autonomous Governments (GADs) of the province of El Oro-Ecuador and the results it generates at the institutional level. The applied method is scientific and has a qualitative-quantitative approach and was delimited as a descriptive-comparative synchronic non-experimental type, the techniques usedare: documentary review and an unpublished database, likewise, the instrument is the minutes of the municipal councils of the province of El Oro, which were collected from institutional sources of the municipal councils from May 24, 2019 to December 31, 2021. The dependent variable is the use of the empty chair and the independent variables are theGADs and the components of public management, which were identified through the reading of the minutes, where this participatory right was used. Among the main results, there was a lack of knowledge of the correct use of the empty chair and its methodological process by the municipalities and the citizens, as well as a lack of participation of women; likewise, the empty chair only influenced decision-making on four occasions